43 'Making human connections' an educational video to engage and promote a culture of inclusivity for clinical and non-clinical staff providing end of life care in an acute London NHS Trust. Issue Volume 11: Issue (2021)Supplement 1 (16th March 2021) - Powell, Kate; MacDonald, Sarah; Wood, Jessica
Abstract : Background: Health professionals and ancillary staff have a unique opportunity to make a positive difference to the end of life (EOL) experiences of their patients and those who are important to them. In order to do so, they need to be equipped with a range of skills, knowledge, attitudes and behaviours. The End of Life Care Core Skills Education and Training Framework sets out the skills and knowledge to achieve this. This framework was used to benchmark the current provision of EOL training and education at a London-based NHS Trust and to develop a novel approach to meeting identified gaps. Methods: A task and finish group consisting of members of the Trust's specialist palliative care team and the EOL care clinical leads reviewed the education mapping exercise and identified key areas of focus for the Trust's EOL education and training programme. These were triangulated with other national EOL frameworks, audits and quality standards. Results: The key education themes identified were: 1) personalisation of end of life care (finding out 'what matters most' to each patient); 2) every staff member has a role in EOL care. Non-clinical staff involved with patients at the end of life were identified as one of the key target groups in the EOL education gap analysis. A short video was agreed as the most innovative educational resource with a focus on the core themes for a non-clinical target audience. In collaboration with an external production team, the narratives of ten Trust employees from a diverse range of clinical and non-clinical roles were recorded. Conclusion: This quality improvement initiative sought to innovatively address a gap in EOL education through the development of an educational video with contributions from a diverse range of clinical and non-clinical staff. The next steps are to implement and evaluate the impact of this project.